Pengaruh Waktu Karbonisasi Pada Proses Pembuatan Briket Pelepah Dan Tandan Kosong Kelapa Sawit Dengan Perekat Tepung Tapioka - M Syukri; S Aisyah; M Ardhika; N H Putri (Cered Indonesia Institute, 2023)
Oil palm plantations produce agricultural waste that has no economic value without further processing. This can be avoided by using empty fruit bunches and palm fronds into briquettes. Briquettes are solid fuel that can be used as an alternative energy source. In this study, empty bunches and coconut fronds were used as raw materials and tapioca flour as an adhesive in making briquettes, with variables of carbonization time and adhesive content and the Completely Randomized Design (CRD) method. Characteristic analysis of briquettes was carried out, such as data on water content, ash content, density, compressive strength and burning rate. Based on research, the highest water content in briquettes with a carbonization time of 2.5 hours for 8% adhesive was 9%, while the lowest in briquettes with a carbonization time of 2 hours for 8% adhesive was 6.4%. The highest density in briquettes with a carbonization time of 2.5 hours and 3 hours with 10% adhesive is 0.57 gr/cm3 while the lowest was in briquettes with a carbonization time of 2 hours and 2.5 hours with 6% adhesive, namely 0.52 gr/cm3. The highest compressive strength was in briquettes with a carbonization time of 3 hours with 10% adhesive of 16.46 kg/cm2 while the lowest was for briquettes with a carbonization time of 2 hours with 6% adhesive at 11.22 kg/cm2. The highest burning rate was in 2 hour carbonization time briquettes with 6% adhesive at 0.23 g/minute while the lowest was in 3 hour carbonization time briquettes with 10% tapioca adhesive at 0.11 g/minute.